PROMOTING LEARNER AGENCY AND REFLECTIVE THINKING BY ELIMINATING DIRECT CORRECTIVE FEEDBACK IN WRITING - Fath, Sahnaz Natasya; Sahayu, Wening (LLT Journal: A Journal on Language and Language Teaching, 2022)
Many researchers have examined the implementation of the promotion method toward the agency principle of multicultural theory. However, little has examined the corrective feedback in promoting the tenet. Given the corrective feedback, the learner will be less used of their reflective thinking to promote themselves as an agent. Therefore, this study aimed to promote learners' agency by eliminating the corrective feedback in writing class and encouraging learners' reflective thinking. Three non-formal intermediate learners writing ability is analyzed in this study. The material given was following the syllabus of the course which is expressing of obligation and prohibition. There were three tasks given in this class. The first task is an individual project, the second is a group project, and the third is an individual project. After the learner finished the task the researcher analyzed the learner's writing improvement by analyzing the frequency and the variation of the lexical used and the grammar detail. Using Primary Trait Scoring, the findings pointed out that the writing ability of the learners improved both lexically and grammatically. Besides, the findings also supported that language produced by the learners is complex, dynamics, and more individual. It is expected that this research could be a consideration for educational stakeholders to select the appropriate method for the learners